FRI0316 SERUM ANTI-MITOCHONDRIAL ANTIBODIES IN SYSTEMIC SCLEROSIS RECOGNIZE VARIABLE PYRUVATE DEHYDROGENASE COMPLEX ANTIGENS. (June 2019) - Ceribelli, Angela; Isailovic, Natasa; Gorlino, Carolina; Generali, Elena; Santis, Maria De; Guidelli, Giacomo Maria; Caprioli, Marta; Sarzi-Puttini, Piercarlo; Satoh, Minoru; Selmi, Carlo
Abstract : Background: Serum anti-mitochondrial antibodies (AMA) are the hallmark of primary biliary cholangitis (PBC) and are identified also in systemic sclerosis (SSc) patients with limited variant and serum anti-centromere antibodies (ACA). Indirect immunofluorescence (IIF) shows the cytoplasmic pattern that characterizes AMA positivity, but it is usually performed when a suspect of PBC is already present. Protein-immunoprecipitation (IP) and IP-Western Blot (WB) have the advantage of 1) identify AMA in an early screening phase, before the onset of PBC and liver function abnormalities; 2) detect the proteins that constitute the pyruvate dehydrogenase complex (PDC) complex (the subunits E1α, E1β, E2/E3, and E3BP) which seem to be associated to different risk of PBC onset. Objectives: To determine the prevalence and clinical significance of the PDC complex subunits in AMA positive SSc patients with and without PBC. Methods: Sera from 279 consecutive patients with rheumatic disease (146 with SSc, 77 with undifferentiated connective tissue disease –UCTD-, and 56 with polymyositis/dermatomyositis -PM/DM) were tested by protein-IP for the screening of serum autoantibodies. In 58/279 (21%) sera we report a complete or partial protein-IP pattern of 75-50-40-34kD bands corresponding to the 4 proteins of the PDC complex recognized by AMA. In these sera we performed IIF and IP-WB to confirm the identity of these bands, by using established protocols. Clinical charts were used to analyze clinical and laboratory data for possible statistical correlation. Results: In 15/58 (26%) patients with protein-IP AMA pattern we confirm a diagnosis of PBC, and all of them had a diagnosis of SSc without additional rheumatic disease. Their expression of the PDC subunits is variable by IP-WB (Figure panel A), but this variability is not associated with specific clinical and laboratory features. In the 42/58 (72%) cases with AMA protein-IP pattern but without clinical and histological evidence of PBC, the E2 component of the PDC was detected in all except one patient, while the expression of the other proteins of the PDC was significantly less represented, i.e. E3BP in 14/42 (33%), E1β in 13/42 (31%), E3 in 6/42 (14%), and E1α in 4/42 (10%) patients. The IIF analysis on Hep2 cells of AMA positive samples also shows different patterns of expression, which spans from cytoplasmic positive staining with a reticular pattern in AMA positive sera for all the PDC proteins recognized by AMA, to cytoplasmic speckled pattern in cases with incomplete expression of PDC antigens (Figure panel B). So far, no specific clinical correlation was identified in these patients, as they did not have a diagnosis of PBC or other autoimmune liver disease or manifested elevated liver function tests. Conclusion: The expression of the PDC antigenic components is variable both in SSc patients with AMA positive PBC and in SSc patients AMA positive without PBC or altered liver function tests, but we could not identify a clinical significance of this variability. It may be necessary to maintain a strict follow-up of these patients and to perform longitudinal studies to determine the prognostic value of this variable expression of PDC components in the onset of PBC. References: [1] Fujimoto M, et al. Arthritis Rheum. 1995Jul; 38(7): 985-9 [2] Ceribelli A, et al. J Immunol Methods. 2018Jan; 452: 1-5 Disclosure of Interests: Angela Ceribelli: None declared, Natasa Isailovic: None declared, Carolina Gorlino: None declared, Elena Generali: None declared, Maria De Santis: None declared, Giacomo Maria Guidelli: None declared, Marta Caprioli: None declared, Piercarlo Sarzi-Puttini: None declared, Minoru Satoh: None declared, Carlo Selmi Grant/research support from: AbbVie, Janssen, MSD, Novartis, Pfizer, Consultant for: AbbVie, Alfa-Sigma, Biogen, Bristol-Myrs Squibb, Celgene, Eli-Lilly, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, UCB, Speakers bureau: AbbVie, Alfa-Sigma, Biogen, Bristol-Myrs Squibb, Celgene, Eli-Lilly, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, UCB